Etika Kristen dalam Pendidikan Karakter dan Moral Siswa di Era Digital [Christian Ethics in Teaching Character and Moral for Students in the Digital Era] - Sioratna Puspita Sari; Jessica Elfani Bermuli (Diligentia: Journal of Theology and Christian Education, 2021)
The development of technology has driven progress in various aspects of human life, especially in the field of education. However, this progress is not always accompanied by significant developments in morality. Various student behaviours related to the use of digital technology indicate the degradation of character and morals. In addition, the phenomenon of relativity makes the problem of morality increase complexity. This makes the importance of building character and moral education based on the truth of God as a source of true moral character. This paper intends to study the importance of Christian ethics in character and moral education in the digital age by literature. The Christian ethical philosophy is a philosophical basis that builds character and moral education based on the character of Christ. This character exists to restore and transform students to living in Christ. So, the concept of Christian ethical philosophy is important to be the philosophical underlying foundation of character and moral education. Suggests that, philosophical of the concept of Christian ethics needs to be realized in character education. Parents with educators collaborate in the monitoring of children's character.